Counterintuitive Wetting Transitions in Doubly Reentrant Cavities as a Function of Surface Make‐Up, Hydrostatic Pressure, and Cavity Aspect Ratio. Issue 22 (7th October 2020) - Arunachalam, Sankara; Ahmad, Zain; Das, Ratul; Mishra, Himanshu
Abstract: Surfaces that entrap air underwater serve numerous practical applications, such as mitigating cavitation erosion and reducing frictional drag. These surfaces typically rely on perfluorinated coatings. However, the non‐biodegradability and fragility of the coatings limit practical applications. Thus, coating‐free, sustainable, and robust approaches are desirable. Recently, a microtexture comprising doubly reentrant cavities (DRCs) has been demonstrated to entrap air on immersion in wetting liquids. While this is a promising approach, insights into the effects of surface chemistry, hydrostatic pressure, and cavity dimensions on wetting transitions in DRCs remain unavailable. In response, Cassie‐to‐Wenzel transitions into circular DRCs submerged in water are investigated and compared with those in cylindrical "simple" cavities (SCs). It is found that at low hydrostatic pressures (≈50 Pa), DRCs with hydrophilic (θo ≈ 40°) and hydrophobic (θo ≈ 112°) make‐ups fill within 10 5 and 10 7 s, respectively, while SCs with hydrophilic make‐up fill within <10 −2 s. Under elevated hydrostatic pressure ( P ≤ 90 kPa), counterintuitively, DRCs with hydrophobic make‐up fill dramatically faster than the commensurate SCs. This comprehensive report should provide a rational framework for harnessing microtexturing and surface chemistry toward coating‐free liquid repellency. Abstract : In this article pressure‐induced wetting transitions inside doubly reentrant and simple cylindrical cavities immersed in water are investigated. A broad set of experimental techniques and mathematical modeling are utilized to unravel the specific contributions of microtexturing, surface make‐up, and hydrostatic pressure towards promoting/preventing Cassie‐to‐Wenzel transitions. Strengths and weaknesses of doubly reentrant cavity microtextures are pointed out.